Structural determinants and genetic modifications enhance BMP2 stability and extracellular secretion. Issue 3 (2nd January 2019) - Khattar, Vinayak; Lee, Joo Hyoung; Wang, Hong; Bastola, Soniya; Ponnazhagan, Selvarangan
Abstract: The short half‐life and use of recombinant bone morphogenetic protein (BMP)2 in large doses poses major limitations in the clinic. Events regulating posttranslational processing and degradation of BMP2 in situ, linked to its secretion, have not been understood. Toward identifying mechanisms regulating intracellular BMP2 stability, we first discovered that inhibiting proteasomal degradation enhances both intracellular BMP2 level and its extracellular secretion. Next, we identified BMP2 degradation occurs through an ubiquitin‐mediated mechanism. Since ubiquitination precedes proteasomal turnover and mainly occurs on lysine residues of nascent proteins, we systematically mutated individual lysine residues within BMP2 and tested them for enhanced stability. Results revealed that substitutions on four lysine residues within the pro‐BMP2 region and three in the mature region increased both BMP2 stability and extracellular secretion. Structural modeling revealed key lysine residues involved in proteasomal degradation occupy a lysine cluster near proprotein convertase cleavage site. Interestingly, mutations within these residues did not affect biological activity of BMP2. These data suggest that preventing intracellular proteasomal loss of BMP2 through genetic modifications can overcome limitations related to its short half‐life.